Visual Modeling Language for Agent Treasury Pharmaceutical - عفاف بديع القدو (College of Education for Women, 2019)
The researches to discover useful ways to represent the agents and agent-based systems are continuous. Unified Modeling Language (UML) is a visual modeling language used for software and non software modeling systems. The aim of this paper is: using UML class diagram to design treasury pharmaceuticals agent and explain its internal action. The diagram explains the movement of the agent among other nodes to achieve user's requests (external) after it takes them. The paper shows that it is easy to model the practical systems by using agent UML when they are used in a complex environment.